PENGARUH INTERNET FINANCIAL REPORTING TERHADAP KEPUTUSAN INVESTASI (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016 ) - M. Riduan Abdillah (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2017)
Abstract,This research aims to examine the effect of Internet Financial Reporting (IFR) on investment decisions. The population in this research are all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2016. Sampling of this research using purposive sampling method.This research independent variable is Internet Financial Reporting (IFR) measured with Internet Disclosure Index (IDI) (Spanos and Mylonakis, 2006), dependent variable is investment decision measured by market to book value of assets (Prapaska, 2012), control variable is firm size measured by the total natural logarithm of company asset (Puspitaningrum and Atmini, 2012; Siagian, et al.2013).The findings found evidence that Internet Financial Reporting (IFR) is unfavorable to investment decisions as well as firm size as a control variable influencing investment decisions.